Design and Analysis of a Bio-Inspired Wire-Driven Multi-Section Flexible Robot. (24th April 2013) - Li, Zheng; Du, Ruxu
This paper presents a bio-inspired wire-driven multi-section flexible robot. It is inspired by the snake skeleton and octopus arm muscle arrangements. The robot consists of three sections and each section is made up of several identical vertebras, which are articulated by both spherical joints and a flexible backbone. Each section is driven by two groups of wires, controlling the bending motion in X and Y directions. This design integrates the serpentine robots' structure and the continuum robots' actuation. As a result, it is more compact than traditional serpentine robots and has a higher positioning accuracy than typical continuum soft robots, such as OctArm V. A Kinematics model and a workspace model of the robot are developed based on the piece wise constant curvature assumption. To evaluate the design, a prototype is built and experiments are carried out. The average distal end positioning error is less than 4%. Characteristics of the wire-driven robot are also discussed, including the leverage effect and the manipulability under constraint. These features makes the proposed robot well suited to confined spaces, especially for working in minimally invasive surgery, nuclear reactor pipelines, disaster debris, etc.